Pollination of Apis mellifera L. on the quality and quantity of Mexican lime - Silva-Jiménez, Elvira; Macias-Macias, José Octavio; Acosta-Núñez, Celine (Revista Mexicana de Ciencias Agrícolas, 2026)
Honeybees (Apis mellifera L.) are the most efficient pollinators in cultivated and wild plants, playing an essential role in agricultural production and ecosystem conservation. This research aimed to evaluate the effect of the distance of Apis mellifera L. hives in pollination with honeybees on the quantity and quality of the fruits of the Mexican lime [Citrus aurantifolia (Christm.) Swingle] from March to July 2022, at the Villa Chica farm of the SiCar Farms company, located in the municipality of Tecomán, Colima, Mexico, with an area of 3.75 ha, where eight honeybee colonies were installed; 36 trees were selected and divided into four treatments that consisted of different ranges of distance from the location of the bee colonies and a control group that was isolated: T1 (0-100 m), T2 (101-200 m), T3 (201-300 m), T4 (randomly selected trees excluding pollinators). Treatments T1 and T2 presented a positive effect on the variables of fruit set percentage, fruit weight, polar diameter, juice weight, and number of seeds, compared to the other treatments, so it is recommended to place hives uniformly in the Mexican lime crops at distances not greater than 200 m between them in order to improve pollination activity and obtain fruits in greater quantity and better quality.
Keywords: Apis mellifera; Citrus aurantifolia; fruit set